Quick, expand it!

Algebra Level 2

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) = 1680 \large (x-7)(x-3)(x+5)(x+1)=1680

Find the sum of all x x that satisfy the equation above.


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Nihar Mahajan
Apr 19, 2015

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) = 1680 (x-7)(x-3)(x+5)(x+1)=1680

( x 7 ) ( x + 5 ) ( x 3 ) ( x + 1 ) = 1680 (x-7)(x+5)(x-3)(x+1)=1680

( x 2 2 x 35 ) ( x 2 2 x 3 ) = 1680 (x^2-2x-35)(x^2-2x-3)=1680

Let x 2 2 x = a x^2-2x=a

( a 35 ) ( a 3 ) = 1680 (a-35)(a-3)=1680

a 2 38 a + 105 1680 = 0 a^2-38a+105-1680=0

a 2 38 a 1575 = 0 a^2-38a-1575=0

( a 63 ) ( a + 25 ) = 0 (a-63)(a+25)=0

a = 63 o r a = 25 \Rightarrow a = 63 \quad or \quad a = -25

When a = 25 x 2 2 x + 25 = 0 x = 2 ± 96 2 a=-25 \Rightarrow x^2-2x+25=0 \Rightarrow x=\dfrac{2\pm\sqrt{-96}}{2} which are complex roots .

When a = 63 x 2 2 x 63 = 0 a=63 \Rightarrow x^2-2x-63=0 , the discriminant is positive.

Hence by Vieta's formula , sum of all roots = 2 + 2 = 4 =2+2\huge=\boxed{4}

Cheers! xD

Moderator note:

There's a simpler way to do. Can you find it?

Easiest way i guess is

( x 2 2 x 35 ) ( x 2 2 x 3 ) = x 4 4 x 3 ± others (x^2-2x-35)(x^2-2x-3) = x^4-4x^3 \pm \text{others}

So by vietas we get the sum of all roots as 4 \boxed{4}

siddharth bhatt - 6 years, 1 month ago

Log in to reply

Ok , I understood , thanks a lot!

Nihar Mahajan - 6 years, 1 month ago

(As pointed out by Siddharth below)

Note that you could have applied Vieta's formula right from the start. For any k k , the sum of all roots to

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) = k (x-7)(x-3) (x+5)(x+1) = k

will be the negative of the cubic term, IE ( 7 3 + 5 + 1 ) = 4 - ( -7 -3 + 5 + 1 ) = 4 .


If you were looking for just real roots, then of course we will need a different approach.

Calvin Lin Staff - 6 years, 1 month ago

Log in to reply

Yeah , the question asks for all roots. But if the question had asked for only real roots , my method would have been more appropriate. Thanks Sir! @Calvin Lin So you are the challenge master? (Just asking for curiosity)

Nihar Mahajan - 6 years, 1 month ago

Oh haha! It's the cubic term, not the linear term.

Pi Han Goh - 6 years, 1 month ago

what difference btw approaching for 'all root' and 'only real root'. in both we will look coeff of x^3??

Riya Verma - 1 year, 9 months ago

Every body has done the same way nihar has, yet nobody has upvoted his solution

:(

Vaibhav Prasad - 6 years, 1 month ago

I don't know why but whenever I put this equation in my calculator it gives me the values of X as -7 and 9.

Harshit Sharma - 6 years, 1 month ago

Log in to reply

Yeah , your calculator is right. Those are the integer roots for the given equation. What's wrong then?

Nihar Mahajan - 6 years, 1 month ago

Log in to reply

How come the answer is 4 whereas it should be 2 because -7 plus 9=2

Harshit Sharma - 6 years, 1 month ago

Log in to reply

@Harshit Sharma Because there are complex roots too. See my solution.

Nihar Mahajan - 6 years, 1 month ago

Cheers! @Nihar Mahajan xD xD

Mehul Arora - 6 years, 1 month ago

Log in to reply

@Pi Han Goh Can you give me a hint?

Nihar Mahajan - 6 years, 1 month ago

Log in to reply

@Nihar Mahajan , Is @Pi Han Goh the challenge master?

Mehul Arora - 6 years, 1 month ago

I did it your way. I don't know what's the simpler way.

Pi Han Goh - 6 years, 1 month ago

Log in to reply

@Pi Han Goh So you are not challenge master? I am surprised

Nihar Mahajan - 6 years, 1 month ago

Log in to reply

@Nihar Mahajan I wish I am. Then I will delete all the crappy problems in Explore hahah!

Pi Han Goh - 6 years, 1 month ago

Log in to reply

@Pi Han Goh So is it Calvin sir? If yes , @Calvin Lin Sir , please give me a hint. I can't find easier method than this. Thanks!

Nihar Mahajan - 6 years, 1 month ago

why u did'nt applied vieta's formula on 3rd step.....

Pranav Patil - 6 years ago

We are just looking for the sum of the roots of the given equation and here the poser did not asked for sum of real roots. So , simply using the Vieta's formal we get our answer as 4. No need to open the completed brackets just find out the coefficients of x 4 w h i c h i s o b v i o u s l y 1 a n d o f x 3 w h i c h w e c a n o b s e r v e i s 7 + ( 3 ) + 5 + 1 = 4. x^4 which is obviously 1 and of x^3 which we can observe is -7+(-3)+5+1 = -4 . So the answer comes out to be \box 4. \box{4}.

Anurag Pandey - 4 years, 10 months ago
Janaki S
Apr 20, 2015

Suppose, the solutions for the final equation are: a, b, c and d

Then, (x-a)(x-b)(x-c)(x-d) = 0

x^4 - (a+b+c+d)x^3+ .... +abcd = 0

The given equation is: (x-7)(x-3)(x+5)(x+1)-1680 = 0

The co-efficients in both the equations have to be same. Taking co-efficients of x^3:

(a+b+c+d) = (7+3-5-1) = 4

Ujjwala Ananth
Jun 20, 2015

After expansion, coefficient of x^3 is -4 and that of x^4 is 1. (-b/a) gives sum of roots, which is -(-4/1) = 4

Simple and elegant !

Anurag Pandey - 4 years, 10 months ago
Ankith A Das
Apr 20, 2015

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) = 1680 x 4 4 x 3 34 x 2 + 76 x 1575 = 0 B y v i e t a s f o r m u l a s u m o f r o o t s = 4 \left( x-7 \right) \left( x-3 \right) \left( x+5 \right) \left( x+1 \right) =1680\\ \Rightarrow { x }^{ 4 }-{ 4 }x^{ 3 }-{ 34 }x^{ 2 }+76x-1575=0\\ By\quad vieta's\quad formula\quad \\ sum\quad of\quad roots=4

Moderator note:

You don't actually need to find the coefficient of the other terms other than x 3 x^3 because we are only interested in finding the sum of roots.

Eamon Gupta
Jan 1, 2018

Note that to find the sum of the solutions we must find a n 1 a n \frac{a_{n-1}}{a_{n}} where a n 1 a_{n-1} is the coefficient of x 3 x^3 and a n a_{n} is the coefficient of x 4 x^4 . The x 4 x^4 coefficient is clearly 1. There are only 4 x 3 x^3 terms when the brackets are expanded, each formed by multiplying the x x terms in 3 of the brackets and then multiplying by the constant in the remaining bracket.

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) 1 x 3 (\color{#D61F06}x\color{#333333}-7)(\color{#D61F06}x\color{#333333}-3)(\color{#D61F06}x\color{#333333}+5)(x\color{#D61F06}+1\color{#333333}) \rightarrow \color{#D61F06}1x^3

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) 5 x 3 (\color{#3D99F6}x\color{#333333}-7)(\color{#3D99F6}x\color{#333333}-3)(x\color{#3D99F6}+5\color{#333333})(\color{#3D99F6}x\color{#333333}+1) \rightarrow \color{#3D99F6}5x^3

( x 7 ) ( x 3 ) ( x + 5 ) ( x + 1 ) 3 x 3 (\color{#20A900}x\color{#333333}-7)(x\color{#20A900}-3\color{#333333})(\color{#20A900}x\color{#333333}+5)(\color{#20A900}x\color{#333333}+1) \rightarrow \color{#20A900}-3x^3

( x 7 ) ( x 7 ) ( x 3 ) ( x + 5 ) 7 x 3 (x\color{#EC7300}-7\color{#333333})(\color{#EC7300}x\color{#333333}-7)(\color{#EC7300}x\color{#333333}-3)(\color{#EC7300}x\color{#333333}+5) \rightarrow \color{#EC7300}-7x^3

The x 3 x^3 term is therefore 1 x 3 + 5 x 3 + ( 3 x 3 ) + ( 7 x 3 ) = 4 x 3 \color{#D61F06}1x^3 +\color{#3D99F6}5x^3 +\color{#20A900}(-3x^3) +\color{#EC7300}(-7x^3) = \color{#333333}-4x^3

Therefore the sum of solutions is 4 1 = 4 -\frac{-4}{1} = \boxed{4}

Carsten Meyer
Apr 9, 2021

The first of Newton's Identities is the way to go, of course, but you can also define x : = y + 1 x:=y+1 to get an even polynomial P ( y ) P(y) : 1680 = ( y 6 ) ( y 2 ) ( y + 6 ) ( y + 2 ) = ( y 2 4 ) ( y 2 36 ) P ( y ) : = y 4 40 y 2 1536 = 0 1680=(y-6)(y-2)(y+6)(y+2)=(y^2-4)(y^2-36)\quad\Rightarrow\quad P(y):=y^4-40y^2-1536=0 By symmetry, P ( y ) P(y) has the roots y 1 , 2 = ± a , y 3 , 4 = ± b , a , b C y_{1,2}=\pm a,\:y_{3,4}=\pm b,\quad a,\:b\in\mathbb{C} , so they cancel each other out in the sum k = 1 4 x k = k = 1 4 ( 1 + y k ) = 4 + k = 1 4 y k = 4 + 0 = 4 \sum_{k=1}^4 x_k=\sum_{k=1}^4(1+y_k)=4+\sum_{k=1}^4 y_k =4+0=\boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...